Chronic Liver Disease Self‐Management for Veterans: A Feasibility Trial - Carol Gonzalez; Ann Deioma; Heather M. Patton; Erik J. Groessl (Lifestyle Medicine, 2026)
ABSTRACT Background Rates of chronic liver disease (CLD) related to obesity and other cardiometabolic risk factors have increased dramatically and contribute to significant health burden and mortality. Lifestyle modification is commonly recommended, with a focus on nutrition, exercise, medication adherence, screening for CLD complications, and active participation in health care. Self‐management interventions can facilitate lifestyle modification in patients with chronic diseases, including CLD. This study tested the feasibility and acceptability of a cognitive behaviorally based self‐management intervention for veterans with CLD. Methods Fourteen veterans participated in a CLD self‐management workshop. Feasibility benchmarks included 75%+ retention rate at initial follow‐up assessment, 50%+ attendance rate, and 75%+ of participants satisfied with the intervention. Results All feasibility benchmarks were met. Overall attendance in classes was 75%, 100% of participants were retained at the 4‐week assessment, and 79% were retained at the 8‐week assessment, and over 90% of participants agree or strongly agree to being satisfied with various aspects of the program. Results suggest that the intervention may produce positive trends in CLD knowledge, health behavior, quality of life, and mental health. Conclusions This pilot study demonstrated that the CLD self‐management class itself was feasible and accepted by participants. A larger randomized controlled trial is needed to establish the efficacy of CLD self‐management.